PERAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI INOVATOR DALAM MENINGKATKAN MOTIVASI KERJA GURU - LindaKharisma; Lilis Kholisoh Nuryani; Sumiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The leadership role of school principals as innovators has a crucial role in creating an innovative environment to increase teachers' work motivation. This type of research is a literature review (literature review), with stages namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling discussions, drawing conclusions based on the results of the analysis. The conclusion of this study is that school principals as innovators have an important role in creating a dynamic and progressive educational environment. To carry out this role, the principal needs to have a strategy that involves harmonizing with the environment, finding new ideas, integrating activities, setting an example, and developing innovative learning models. In addition, the principal must be able to find, find, and implement updates in the school, as well as optimize the available resources. This is closely related to teacher motivation because motivation has a considerable influence on a person's performance. If they have an interest in a job, a person will complete the work according to the demands of their institution.